Assessment of myocardial deformation with CMR: a comparison with ultrasound speckle tracking in a cohort of highly trained endurance athletes. (8th February 2021) - Domenech-Ximenos, B; Sanz-De La Garza, M; Sepulveda-Martinez, A; Lorenzatti, D; Simard, F; Crispi, F; Perea, RJ; Prat-Gonzalez, S; Sitges, M
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Plan Nacional I.D., Del Programa Estatal de Fomento De La Investigación Científica y Técnica de Excelencia, Subprograma De Generación Del Conocimiento, Ministerio de Economía y Competitividad 2013. Background:  Myocardial deformation integrated with cardiac dimensions provides a comprehensive assessment of the ventricular remodelling patterns induced by cumulative effects of intensive exercise. Feature tracking(FT) can measure myocardial deformation from cardiac magnetic resonance(CMR) cine sequences; however, its accuracy is still scarcely validated. Purpose:  Our aim was to compare FT's accuracy and reproducibility to speckle tracking echocardiography (STE) in highly trained endurance athletes (EAs). Methods:  93 EAs (>12 hours training/week during the last 5 years, 52% male, 35 ± 5.1 years) and 72 age-matched controls underwent a resting CMR and a transthoracic echocardiography to assess biventricular exercise-induced remodelling and biventricular global longitudinal strain (GLS) by CMR-FT and STE. Results:   High endurance training load was associated with larger bi-ventricular and bi-atrial sizes and mildly reduced systolic function of both ventricles (p < 0, 05). Strain values (both by CMR-FT and STE) proportionally decreased with increasing ventricular volumes potentially depicting the increased volume and functional biventricular reserve that characterize EAs heart. Strain values were lower when assessed by CMR-FT as compared to STE (p < 0.001), with good reproducibility for the LV (bias = 3.94%, LOA= ± 4.27%) but wider variability for RV strains (Figure 2). Conclusions:   Biventricular longitudinal strain values were lower when assessed by FT compared to STE. Both methods were comparable when measuring LV strain but not RV strain. These differences might be justified by FT's lower in-plane spatial and temporal resolution, which is particularly relevant for the complex anatomy of the RV.